The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/hec.3157
|View full text |Cite
|
Sign up to set email alerts
|

Do High Consumers of Sugar‐Sweetened Beverages Respond Differently to Price Changes? A Finite Mixture IV‐Tobit Approach

Abstract: This study compares the impact of sugar-sweetened beverages (SSBs) tax between moderate and high consumers in Australia. The key methodological contribution is that price response heterogeneity is identified while controlling for censoring of consumption at zero and endogeneity of expenditure by using a finite mixture instrumental variable Tobit model. The SSB price elasticity estimates show a decreasing trend across increasing consumption quantiles, from -2.3 at the median to -0.2 at the 95th quantile. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 33 publications
(33 reference statements)
5
44
0
Order By: Relevance
“…were lower for high, compared to moderate, consumers of SSBs, suggesting that high consumers are less likely to be affected by price changes (7) . However, this does not imply that the tax would not affect high consumers, as this group consumes more SSBs in absolute terms than moderate consumers.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…were lower for high, compared to moderate, consumers of SSBs, suggesting that high consumers are less likely to be affected by price changes (7) . However, this does not imply that the tax would not affect high consumers, as this group consumes more SSBs in absolute terms than moderate consumers.…”
Section: Discussionmentioning
confidence: 92%
“…However, a number of gaps in the literature have been identified that warrant further investigation. First, the effect of the tax could be lower among high consumers of SSBs (7) and higher among groups with low socio-economic profiles (5) .…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, definitions included products high in caffeine or products that had been subjected to intensive processing, such as processed meat [15]. For non-alcoholic beverages, the most common targets of taxes were SSBs, which can include soft drinks or soda, cordials, other sugar-added juices, and ‘isotonics’ [1618]. A small number of studies also included milk-based products (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…An SSB tax would be especially beneficial for younger individuals, males, and those with low income (i.e. the main SSB consumers), and could thus be valuable with regard to health equity, too [35]. Future studies should focus on this age group to assess benefits but also potential risks of an SSB tax.…”
Section: Discussionmentioning
confidence: 99%